The Influence of Hot-Dip Galvanizing on the Mechanical Properties of High Strength Steels - Šmak, Milan; Kubíček, Jaroslav; Kala, Jiří; Podaný, Kamil; Vaněrek, Jan (MDPI, 2021)
Modern high-strength steels achieve their strength exclusively through the manufacturing process. Typically, hot-dip galvanizing is used to form a protective zinc layer on the steel parts of structures; nonetheless, the material is exposed to high temperatures during the process. This study aims to experimentally examine and evaluate the extent of change of the mechanical properties of high-strength-steel members. The effect was studied on specimens made of different types of steel with the yield strength ranging from 460 to 1250 MPa. For each type of steel, selected mechanical propertieswere determined on specimens with and without hot-dip galvanization, and the obtained results were mutually compared. Our study shows a significant impact of the hot-dip galvanization process on the mechanical properties of some high-strength steels.

Modern high-strength steels achieve their strength exclusively through the manufacturing process. Typically, hot-dip galvanizing is used to form a protective zinc layer on the steel parts of structures; nonetheless, the material is exposed to high temperatures during the process. This study aims to experimentally examine and evaluate the extent of change of the mechanical properties of high-strength-steel members. The effect was studied on specimens made of different types of steel with the yield strength ranging from 460 to 1250 MPa. For each type of steel, selected mechanical propertieswere determined on specimens with and without hot-dip galvanization, and the obtained results were mutually compared. Our study shows a significant impact of the hot-dip galvanization process on the mechanical properties of some high-strength steels.
The Influence of Hot-Dip Galvanizing on the Mechanical Properties of High Strength Steels
Keywords: hot-dip galvanizing; zinc coating; high-strength steels; yield strength; tensile strength; hardness; thermal process; hot-dip galvanizing; zinc coating; high-strength steels; yield strength; tensile strength; hardness; thermal process